The Hereditary Basis of Rheumatic Diseases - Holmdahl, Rikard.; Holmdahl, Rikard. (Progress in Inflammation Research,, 2006)
Rheumatoid Arthritis (RA) represents a complex disease where the inheritable component has been estimated to be up to 60%. This PIR volume deals with the genetic basis and regulation of rheumatic diseases. The first part of the book describes genetic studies on rheumatic diseases. The second part deals with the shared heredity of rheumatic diseases, e.g., RA, lupus and ankylosing spondylitis. The third part of the volume describes tools for analysing genetic complexity, ranging from animal models to new molecular tools. The volume is essential reading for researchers and clinicians from rheumatology, inflammation research, immunology, and cell and molecular biology. .